EMPOWERMENT OF STUDENTS TO MANAGE THE SCHOOL HEALTH UNIT IN THE PREVENTION OF INFECTIOUS DISEASES - Saraswati Laksmi Dewi; Putu Shinta Widari Tirka; I Gusti Ayu Agung Istri Sari Dewi; Sri Masyeni; Previyanti Dharma; Putu Indah Kusumadewi Riandra (LPPM Universitas Flores, 2026)
Students who manage school health units often have limited knowledge of infectious diseases and health literacy. This program aims to enhance students' understanding of infectious diseases and health literacy skills at Payangan 1 State Senior High School, who oversee the school's health unit. To achieve this, the community service program at Payangan 1 State Senior High School uses an outreach approach and health literacy-focused demonstrations. The partners in this initiative include students managing the school's health unit, supportive teachers, and health professionals. The PKM consists of several stages, including material preparation. Counselling sessions on infectious diseases (such as HIV, dengue fever, and tuberculosis) for the school's health unit management students, utilizing presentations and focus group discussions. Improvement of the school's health unit facilities and distribution of personal protective equipment (PPE). Counselling on materials related to adolescent entrepreneurship. To evaluate the program's effectiveness, pretests and posttests were administered to measure changes in knowledge of infectious diseases and health literacy. The results showed a 65.1% increase in knowledge about infectious diseases and a 50% increase in health literacy. It is anticipated that this program will positively impact students' physical, mental, and social health, create a healthier school environment, and empower students to become agents of change within their communities.